1980
DOI: 10.1111/j.1476-5381.1980.tb10695.x
|View full text |Cite
|
Sign up to set email alerts
|

COMPARATIVE ELECTROPHYSIOLOGICAL EFFECTS OF Org 6001, A NEW ORALLY ACTIVE ANTIDYSRHYTHMIC AGENT, AND LIGNOCAINE ON HUMAN VENTRICULAR MUSCLE

Abstract: The electrophysiological effects of Org 6001, a new orally active antidysrhythmic agent, have been compared with those of lignocaine on the human ventricular action potential in vitro. 2 Org 6001 (4 to 16 mg/l) greatly reduced the maximum rate of depolarization (MRD) of the human ventricular action potential but had no effect on resting membrane potential or action potential amplitude. 3 The action potential duration at the 50% repolarization level, but not at the 90% repolarization level, was significantly re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Studies on human ventricular muscle (Kane, 1980) have shown that lignocaine differs from Org 6001 (and quinidine) in its actions on absolute refractory period. However until the genesis of ventricular fibrillation is better understood, the relevance of these subtle differences in the electrophysiological profile of Class I antiarrhythmic drugs remains unclear.…”
Section: Methodsmentioning
confidence: 99%
“…Studies on human ventricular muscle (Kane, 1980) have shown that lignocaine differs from Org 6001 (and quinidine) in its actions on absolute refractory period. However until the genesis of ventricular fibrillation is better understood, the relevance of these subtle differences in the electrophysiological profile of Class I antiarrhythmic drugs remains unclear.…”
Section: Methodsmentioning
confidence: 99%
“…Lidocaine treatment prolonged the APD and slowed Vmax in human ventricular muscle preparations [232]. In hiPSC-CMs, lidocaine blocked Na + influx and decreased conduction velocity but did not affect the APD [233].…”
Section: Cardiac Cell Maturitymentioning
confidence: 99%
“…Vaughan Williams & Wittig, 1976;Kane, 1980). CCI 22277 was developed more recently and shown to be more potent than Org 6001 at suppressing aconitine- CH3 ,CH ( () The Macmillan Press Ltd 1982 induced arrhythmias in the rat (Dodds, Dolamore, Sawyer, Straughan & Twissel, 1982).…”
Section: Introductionmentioning
confidence: 99%